La Encíclica Sollicitudo rei socialis y la preocupación de Juan Pablo II por el desarrollo de los pueblos. Reflexión en el 25 aniversario de la encíclica Sollicitudo rei socialis - Robert Kantor (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The Catholic Church’s teaching on the development of the nations is generally included in two documents: Populorum Progressio by Pope Paul VI and Sollicitudo rei socialis by John Paul II. This year marks the 25 th anniversary of publishing the Encyclical Sollicitudo rei socialis, hence the motive for writing this article. A characteristic feature of the teaching of John Paul II, which we fi nd in this Encyclical, is the ethical dimension of development. The Pope repeatedly drew attention to the inequitable distribution of material goods in the world. He stressed that “True development, in keeping with the speci fi c needs of the human being – man or woman, child, adult or old person implies, especially for those who actively share in this process and are responsible for it, a lively awareness of the value of the rights of all and of each person. It likewise implies a lively awareness of the need to respect the right of every individual to the full use of the bene fi ts offered by science and technology” Sollicitudo rei socialis 33. This article consists of the four following issues: 1. Populorum Progressio and a new analysis on the development of the nations; 2. The main motive for the publication of Sollicitudo rei socialis ; 3. The concept of development in the teaching of John Paul II; 4. Topicality of the papal document – 25 years later.